FELDA Ventures Holdings Berhad (FGV) involvement in cross border palm oil plantation ventures: Challenges and prospects - Masum, Ahmad; Md Dahlan, Nuarrual Hilal; Md Desa, Md Rejab; Mohd Khalid, Al Hanisham (2015)
Malaysia currently accounts for 39% of world palm oil production and 44% of world exports. Being one of the biggest producers and exporters of palm oil, Malaysia has an important role to play in fulfilling the growing global demand for palm oil. With the growing global demand for palm oil, Malaysian Multinational Enterprises (MNEs) have embarked on the expansion of palm oil plantations by involving in cross border palm oil plantation ventures but encountering numerous challenges.The aim of this paper is to examine the challenges and prospects faced by FELDA Ventures Holdings Berhad in cross border palm oil plantation ventures with Indonesia as a host country.The methodology adopted in this paper is a legal library based research focusing mainly on primary and secondary legal sources.The paper concludes that there are several challenges faced by FELDA Ventures Holdings Berhad such as the absence of a comprehensive and adequate legal guide model for cross border palm oil plantation ventures involving Malaysian MNEs, absence of a dual approach to help address threats related to foreign direct investment in agricultural land, culture of patronage politics, etc. Regardless of these challenges, the future looks bright in terms of prospects in the operation of FELDA Ventures Holdings Berhad.